CTS AND PHYSICAL EDUCATION IN THE BNCC: POSSIBILITIES AND INTERRELATIONSHIPS (VERUM: Journal of Scientific Initiation, 2024)
The Science, Technology, and Society (STS) movement emerged from the academic community in opposition to the technocratic view of science and technology. However, the literature shows a silence when correlating Physical Education (PE) with the STS movement. In this sense, this study aimed to explore interrelationships between the STS movement and PE in the National Common Curricular Base (BNCC), seeking possibilities for joint action. In our searches, we found only one study that correlated the two areas of focus in this review. Despite this limitation, we observe that the integration of PE and STS is feasible and can provide an alternative foundation for PE research. PE is capable of appropriating the concepts of the STS movement, as these are aligned with the BNCC. Finally, more studies are needed to elucidate how the dynamics of pedagogical theories and the STS movement have evolved over time in Brazil and their developments in educational proposals.
Keywords: National Common Curricular Base; Law of Guidelines and Bases of Education; History Teaching; Civil Society; Education